Standardized fetal anatomical examination using magnetic resonance imaging: a feasibility study. (2nd October 2013) - Millischer, A. E.; Sonigo, P.; Ville, Y.; Brunelle, F.; Boddaert, N.; Salomon, L. J.
ABSTRACT: Objective: To determine whether a standard complete fetal anatomical survey, as recommended for ultrasound examination guidelines, is feasible using a standardized magnetic resonance imaging (MRI) protocol . Methods: Based on guidelines for ultrasound examination, we created a specific MRI protocol for fetal anatomical survey. This protocol was then tested prospectively in 100 women undergoing fetal MRI examination for various specific indications at a median gestational age of 30 weeks. The feasibility of using MRI to perform the fetal anatomical survey was analyzed by two reviewers (A and B) based on 26 predefined anatomical criteria, yielding a score ranging from 0 to 26 (26 meaning successful complete anatomical study). Reproducibility was analyzed using percentage agreement and modified kappa statistics . Results: The mean score for the standardized MRI anatomical survey was 24.6 (SD, 1.4; range, 15–26) for Reviewer A and 24.2 (SD, 1.7; range, 15–26) for Reviewer B ( P  = 0.1). Twenty‐two, two and two criteria could be assessed in > 95%, 80–95% and < 80% of cases by Reviewer A and 19, four and three criteria could be assessed in > 95%, 80–95% and < 80% of cases by Reviewer B. For both reviewers, the two most difficult criteria to evaluate were aorta and pulmonary artery. Inter‐reviewer agreement was above 90% for 22 of the 26 anatomical criteria and adjusted kappa coefficients for each criterion demonstrated good, moderate and poor agreement for 22, two and two criteria, respectively . Conclusion: Our data support the hypothesis that standardized fetal anatomical examination might be achieved and reproducible using MRI, although improvement is required for the cardiac part of the examination. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd .